2019
DOI: 10.1111/jopr.13031
|View full text |Cite
|
Sign up to set email alerts
|

A Technique to Simultaneously Fabricate Multiple Custom Impression Posts for Implant‐Supported Restorations in the Esthetic Zone

Abstract: Peri‐implant transmucosal tissue, an essential element of peri‐implant esthetics, is critical to the success of prostheses in the esthetic zone. The optimal transmucosal tissue profile can be transferred to the master cast with the aid of custom impression posts. In this clinical technique, the initial cast used to fabricate provisional prostheses was conveniently used to aid in the time‐efficient fabrication of multiple custom impression posts simultaneously using self‐cured acrylic resin. This technique also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Immediate temporization has advantages including the ability to provide optimal aesthetics by guiding the tissue response during the healing phase, and facilitating the production of final restorations, as well as protecting patients' wellbeing and self-esteem [13,14,16,20]. After removing the temporary crowns, due to the rapid depression of the peri-implant soft tissues, several impression techniques have been reported that duplicate the soft tissue form to the final restoration in a more appropriate method compared with the traditional impression technique [15,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immediate temporization has advantages including the ability to provide optimal aesthetics by guiding the tissue response during the healing phase, and facilitating the production of final restorations, as well as protecting patients' wellbeing and self-esteem [13,14,16,20]. After removing the temporary crowns, due to the rapid depression of the peri-implant soft tissues, several impression techniques have been reported that duplicate the soft tissue form to the final restoration in a more appropriate method compared with the traditional impression technique [15,19].…”
Section: Discussionmentioning
confidence: 99%
“…The indirect technique that requires extra-oral additions of resin to impression posts reflects completely the form of the peri-implant mucosa surrounding the temporary crowns and allows delivery to the laboratory [15,18,19]. The primary benefit of the extraoral acrylic resin addition is the none of connection of the resin with the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation